Imagine there are no leaders: Reframing leadership as collaborative agency - Joseph A. Raelin (Leadership, 2016)
Fearing that our overreliance on an individual, heroic model of leadership will only continue to dampen the energy and creativity of people in our organizations and communities, this essay proposes a practice perspective of leadership based on a collaborative agency mobilized through engaged social interaction. After briefly reviewing the emerging practice tradition in leadership studies, the article turns to the inseparable connection between leadership and agency and discusses how structure may pacify but, under dialogic conditions, release agency. Acknowledging the cultural constraints against collaborative agency, the account affirms its potential realization through interpersonal interaction and sociality. Specific leadership activities associated with collaborative agency and their conditions are illustrated. The paper concludes by showing how the collaborative agentic model might produce a more sustainable future for our world while suggesting avenues for future research of a collective rather than a personal approach to leadership.
Keywords: J24; M10; M12; M14; M53; M54; 330; Leadership; Agency; Collaboration; Collective leadership; Shared leadership; Leaderful practice; Symbolic interactionism; Dialogue; Critical reflection; Meaning making